Dependence of Modulus and Hardness on the Annealing Conditions of Pt57.5Cu14.7Ni5.3P22.5 Bulk Metallic Glass. (17th January 2019) - Chen, Zheng; Datye, Amit; Brooks, P. Aidan; Sprole, Madison; Ketkaew, Jittisa; Sohn, Sungwoo; Schroers, Jan; Schwarz, Udo D.
ABSTRACT: The mechanical properties of metallic glasses are often tuned by annealing, which influences these properties by adjusting the relaxation and/or crystallization status of the glasses. Here, we studied the hardness and modulus of Pt57.5 Cu14.7 Ni5.3 P22.5 bulk metallic glass annealed at different temperatures by nanoindentation, where the annealing gives the material different fictive temperatures and fractions of crystallization. It is found that both reducing the fictive temperature of a fully amorphous sample and increasing the degree of crystallization in a partially crystallized sample increase hardness and modulus. Combining the two approaches, elevated hardness and modulus values are found for composite materials containing both crystalline and amorphous phases when they are compared to chemically identical alloys featuring similar percentages of crystalline and amorphous phases that have been prepared by annealing at higher temperatures. Our findings indicate that the mechanical properties of the platinum-based alloys can be customized by processing them with targeted heat treatments.